Inorganic artificial stone repairing material and preparation method thereof
Through the synergy between chemically bonded magnesium phosphate-based inorganic gelling materials and retarding, active addition and color-tooling materials, the shortcomings of inorganic artificial stone repair materials in terms of bonding performance, settling time and wear resistance are solved, and high efficiency is achieved , the beautiful repair effect fills the gap in repair materials on the market.
Patent Information
- Application Number
- CN202411428467.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-03
AI Technical Summary
The existing inorganic artificial stone repair materials have shortcomings in bonding performance, settling time, early strength, color adjustment and wear resistance, which are difficult to meet the efficient repair needs of decorative stones, especially in terms of both aesthetics and mechanical properties. Solution.
Using chemically bonded magnesium phosphate-based inorganic gelling materials, magnesite or magnesium grinding powder as magnesium material, combined with retarding materials, inorganic active additive materials and color-tooling materials, optimize the performance of repair materials through synergistic effects , achieve rapid condensation, strength improvement and color consistency, and use quartz sand aggregate to improve the service performance of the material.
It significantly reduces carbon emissions and energy consumption, provides high bonding strength, rapid condensation, wear resistance and aesthetics, and is suitable for a variety of damage types and colors of inorganic artificial stones, improving the overall performance and durability of repair materials.
Smart Images

Figure CN119241202A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of artificial stone repair, and in particular to an inorganic artificial stone repair material and a preparation method thereof. Background Art
[0002] With the development of the building decoration industry, people's demand for decorative materials is growing. Inorganic artificial stone has gradually become a popular choice in the market due to its environmental protection, durability and aesthetic characteristics. Inorganic artificial stone is usually made of natural mineral materials through processing, which can simulate the texture and color of natural stone, and has better processing performance and lower cost.
[0003] At present, inorganic artificial stones on the market mainly use cement, resin, etc. as adhesives, and various products are manufactured by mixing different fillers and pigments. These materials meet the needs of architectural decoration to a certain extent, but in practical applications, when they are damaged or need to be repaired, the existing repair materials are often difficult to perfectly match with the original stone, and the repaired interface is prone to color difference, insufficient strength or poor durability. Like most other decorative stones, inorganic artificial stone is a brittle plate that is prone to brittle failure and cracks due to ground settlement or uneven loading. There are many repair materials and processes in the prior art that are mostly used for road damage. Although they can effectively solve problems such as road cracks and collapse, they all consider practicality and economy. As a decorative stone, inorganic artificial stone still lacks targeted repair materials on the market that can take into account both its mechanical properties and aesthetic properties.
[0004] The main deficiencies of existing repair materials are: 1) The interface bonding performance after repair is insufficient, which easily leads to the formation of a weak layer between the repair area and the original stone, affecting the stability of the overall structure. 2) The setting time of the repair material is relatively long, which is not conducive to rapid repair and commissioning, affecting the construction efficiency of building decoration. 3) The early strength of the repair material is insufficient and cannot withstand loads in a short period of time, limiting its application in some emergency repair situations. 4) The color of the repair material is difficult to adjust and it is difficult to be completely consistent with the color of the original stone, affecting the overall appearance after repair. 5) The wear resistance and weather resistance of the repair material are insufficient, and the repair area is prone to wear or aging, shortening the durability of the repair effect. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide an inorganic artificial stone repair material and a preparation method thereof. The repair material is a chemically bonded magnesium phosphate-based inorganic gelling material. The magnesium material comes from magnesite sintered at about 800°C or brucite ore directly ground into powder. Compared with traditional cement-based repair materials, the carbon emissions are greatly reduced, and the energy consumption and repair costs are significantly reduced. At the same time, inorganic artificial stone, as a cement-based artificial stone, has strong compatibility with the repair material of the present invention, which is specifically manifested in the high interfacial bonding strength between the two, and no obvious weak area will be formed; the repair material of the present invention can solidify and harden in a short time to form strength and start to serve. The retarding materials such as sodium citrate and borax, citric acid and boric acid will complex to form BOC chains, and reduce the dissolution rate of magnesium ions through the steric hindrance effect, showing a synergistic effect; the inorganic active additives in the regulating components provided by the present invention can be used to improve the internal pore structure of the material, fill larger harmful pores, and optimize the physical and chemical properties of the material; the aggregate is selected according to the material, and the quartz sand particle size is selected to be consistent with the aggregate used for the damaged inorganic artificial stone. The selection of continuously graded aggregates can further optimize the service performance of the repair material; the coloring material is pre-mixed into a water-based color paste, which is more operable, easier to control and easier to disperse than adding color powder to the mixing water. In summary, under the synergistic effect of the retarding material, inorganic active additives, aggregates and coloring materials, the service performance and aesthetics of the repair material are taken into account.
[0006] According to a first aspect of the present invention, there is provided an inorganic artificial stone repair material, comprising a repair component and a regulating component, wherein the repair component is measured in percentage by mass and comprises: 40%-80% of a magnesium material and 20%-60% of a phosphorus material; an additional regulating component is added, which, based on 100% by mass of the repair component, comprises: 2%-10% of a retarding material, 2%-10% of an inorganic active additive, 0%-60% of an aggregate, 0%-2% of a coloring material and 12%-25% of mixing water.
[0007] Furthermore, the magnesia material includes one or more of brucite, high temperature fired magnesium-containing ore powder and pure magnesium oxide chemical powder.
[0008] Furthermore, the magnesium materials are all in the form of white powder, and the MgO content in the chemical composition is higher than 50%.
[0009] Furthermore, the phosphorus material is one or more of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, ammonium monohydrogen phosphate, potassium monohydrogen phosphate, and sodium monohydrogen phosphate.
[0010] Furthermore, the chemical purity of the phosphorus materials is higher than 99.0%.
[0011] Furthermore, the retarding material is one or two of borax, boric acid, sodium citrate and citric acid, and the chemical purity of the retarding material is higher than 99.0%.
[0012] Furthermore, the inorganic active additive material in the regulating component is one or both of silica fume and metakaolin, and both are white particles or powders.
[0013] Furthermore, the aggregate is quartz sand with continuous grading and a mesh size range of 10 meshes to 100 meshes.
[0014] Furthermore, the coloring material is one or more of titanium dioxide, iron black powder, iron red powder, iron yellow powder and iron brown powder.
[0015] According to a second aspect of the present invention, there is provided a method for preparing an inorganic artificial stone repair material, comprising:
[0016] S100, weighing the magnesium material and the phosphorus material in the repair component, the retarding material, the inorganic active additive material and the aggregate in the regulating component respectively, mixing them in proportion and stirring them evenly to obtain a solid mixture;
[0017] S200, mixing the coloring material and the dispersion liquid in a mass ratio of 1:1, grinding in advance in a three-roll grinder for 45-120 minutes, and adjusting to a water-based color paste;
[0018] S300, weighing 12%-25% of the mass of the repair component, adding the water-based color paste to the water in small amounts and multiple drops until there is no obvious color difference between the water-based color paste and the inorganic artificial stone, and mixing evenly to obtain a toning solution;
[0019] S400, mixing the solid mixture with the toning solution for 1-3 minutes, during which the color paste can be dripped in small amounts multiple times to fine-tune until there is no color difference, thereby obtaining the inorganic artificial stone repair material.
[0020] Beneficial effects of the present invention:
[0021] 1. The repair material provided by the present invention is a chemically bonded magnesium phosphate-based inorganic gelling material. The magnesium material comes from magnesite sintered at about 800°C or brucite ore directly ground into powder. Compared with traditional cement-based repair materials, the carbon emissions are greatly reduced, and the energy consumption and repair costs are significantly reduced. At the same time, inorganic artificial stone, as a cement-based artificial stone, has strong compatibility with the repair material of the present invention, which is specifically manifested in the high interfacial bonding strength between the two, and no obvious weak area will be formed; the repair material of the present invention can solidify and harden in a short time to form strength and start to serve. The retarding materials such as sodium citrate and borax, citric acid and boric acid will complex to form BOC chains, and reduce the dissolution rate of magnesium ions through the steric hindrance effect, showing a synergistic effect; the inorganic active additives in the regulating components provided by the present invention can be used to improve the internal pore structure of the material, fill larger harmful pores, and optimize the physical and chemical properties of the material; the aggregate is selected according to the material, and the quartz sand particle size is selected to be consistent with the aggregate used for the damaged inorganic artificial stone. The selection of continuously graded aggregates can further optimize the service performance of the repair material; the coloring material is pre-mixed into a water-based color paste, which is more operable, easier to control and easier to disperse than adding color powder to the mixing water. In summary, under the synergistic effect of the retarding material, inorganic active additives, aggregates and coloring materials, the service performance and aesthetics of the repair material are taken into account.
[0022] 2. The repair material provided by the present invention is pure white or a color close to it, and is operable. When matched with a color-adjusting material, it can flexibly repair inorganic artificial stones of various colors without color difference;
[0023] 3. The repair material provided by the present invention has high fluidity, can achieve the goals of self-leveling and self-compacting, and is suitable for various types of damage or cracks of different widths in inorganic artificial stones;
[0024] 4. The repair material provided by the present invention has good wear resistance, acid and alkali resistance, and is suitable for various indoor and outdoor decoration environments.
[0025] Additional aspects and advantages of the present application will be partially given in the following description, which will become apparent from the following description, or will be understood through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0027] Figure 1 It is a method for preparing an inorganic artificial stone repair material in an embodiment of the present invention;
[0028] Figure 2 The invention relates to a method for preparing a traditional inorganic artificial stone repair material in an embodiment of the invention. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention. It should also be noted that, for ease of description, only parts related to the present invention, rather than all structures, are shown in the accompanying drawings.
[0030] Those skilled in the art will appreciate that, unless otherwise stated, the singular forms "a", "an", "said" and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0031] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical terms and scientific terms) used herein have the same meaning as the general understanding of those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as in the context of the prior art, and will not be interpreted with an idealized or overly formal meaning unless specifically defined as in the embodiments of this application.
[0032] The present invention provides an inorganic artificial stone repair material and a preparation method thereof. The repair material is a chemically bonded magnesium phosphate-based inorganic gelling material. The magnesium material comes from magnesite sintered at about 800°C or brucite ore directly ground into powder. Compared with traditional cement-based repair materials, the carbon emission of the repair material is greatly reduced, and the energy consumption and repair cost are significantly reduced. At the same time, inorganic artificial stone, as a cement-based artificial stone, has strong compatibility with the repair material of the present invention, which is specifically manifested in the high interfacial bonding strength between the two, and no obvious weak area will be formed; the repair material of the present invention can solidify and harden in a short time to form strength and start to serve. The retarding materials such as sodium citrate and borax, citric acid and boric acid will complex to form BOC chains, and reduce the dissolution rate of magnesium ions through the steric hindrance effect, showing a synergistic effect; the inorganic active additives in the regulating components provided by the present invention can be used to improve the internal pore structure of the material, fill larger harmful pores, and optimize the physical and chemical properties of the material; the aggregate is selected according to the material, and the quartz sand particle size is selected to be consistent with the aggregate used for the damaged inorganic artificial stone. The selection of continuously graded aggregates can further optimize the service performance of the repair material; the coloring material is pre-mixed into a water-based color paste, which is more operable, easier to control and easier to disperse than adding color powder to the mixing water. In summary, under the synergistic effect of the retarding material, inorganic active additives, aggregates and coloring materials, the service performance and aesthetics of the repair material are taken into account.
[0033] In an embodiment of the present invention, the magnesium material is magnesite sintered at a high temperature of 1600°C and further ground into magnesium oxide powder, with a MgO content greater than or equal to 90% and a specific surface area greater than or equal to 133m2 / kg; the phosphorus material is industrial-grade potassium dihydrogen phosphate with a chemical purity greater than or equal to 99%; the retarding material is industrial-grade borax with a chemical purity greater than or equal to 99%; the inorganic active additive is white silica fume with a SiO2 content greater than or equal to 92%; the aggregate is quartz sand with a mesh size of 20-70 mesh; the coloring material is titanium dioxide and iron black powder. Taking titanium dioxide as an example, the powder and pure water are mixed in a mass ratio of 1:1 and ground by a three-roll grinder for 90 minutes to obtain a white color paste, and a black color paste is obtained in the same way; the mixing water is qualified tap water.
[0034] In the comparative example of the present invention, the repair material includes a main component and a regulating component; the main component is cement; the regulating component includes an inorganic active additive, a water reducing agent, an aggregate, a coloring material and mixing water.
[0035] Furthermore, in the comparative example of the present invention, the cement is P.W52.5 white silicate cement; the inorganic active additive is white silica fume, and the SiO2 content is greater than or equal to 92%; the water reducer is a polycarboxylic acid high-efficiency water reducer; the aggregate is quartz sand with a mesh size of 20-70 mesh; the coloring material is titanium dioxide and iron black powder. Taking titanium dioxide as an example, the powder and pure water are mixed in a mass ratio of 1:1 and ground by a three-roll grinder for 90 minutes to obtain a white color paste, and a black color paste is obtained in the same way; the mixing water is qualified tap water.
[0036] Embodiment 1:
[0037] The embodiment of the present invention provides an inorganic artificial stone repair material. Magnesium material and phosphorus material in the repair component are first weighed by mass percentage, wherein the regulating component is additionally weighed and added based on the mass of the repair component being 100%, as follows:
[0038] Repair components: magnesium oxide powder 75%, potassium dihydrogen phosphate 25%, the sum of the two is 100%.
[0039] Regulating components: borax 5%, white silica fume 5%, white color paste 0.4%, black color paste 0.2%, tap water 17%.
[0040] like Figure 1 As shown, the embodiment of the present invention also provides a method for preparing an inorganic artificial stone repair material, comprising:
[0041] S100, first accurately weigh the magnesium material and phosphorus material in the repair component, then weigh the retarding material, inorganic active additive material and aggregate in the regulating component respectively, mix them according to the proportion, and stir them evenly to obtain a solid mixture.
[0042] S200, mix the coloring material and the dispersion liquid in a mass ratio of 1:1, grind them in a three-roll grinder for 90 minutes in advance, and adjust them into a water-based color paste
[0043] S300, weigh 17% of the mass of the repair component in mixing water, drop the prepared water-based color paste into the water in small amounts and multiple times until there is no obvious color difference with the inorganic artificial stone, and mix evenly to obtain a toning solution.
[0044] S400, mixing the solid mixture with the toning liquid for 2 minutes, during which white color paste or black color paste is added in small amounts and multiple times, and fine-tuned until there is no color difference, to obtain the inorganic artificial stone repair material.
[0045] Example 2
[0046] The inorganic artificial stone repair material proposed by the present invention is firstly weighed according to the mass percentage of the magnesium material and the phosphorus material in the repair component, wherein the regulating component is additionally weighed and added based on the mass of the repair component being 100%, specifically as follows:
[0047] Repair components: magnesium oxide powder 75%, potassium dihydrogen phosphate 25%, the sum of the two is 100%.
[0048] Regulating components: borax 5%, white silica fume 5%, quartz sand 20%, white color paste 0.4%, black color paste 0.2%, tap water 17%.
[0049] like Figure 1 As shown, the embodiment of the present invention also provides a method for preparing an inorganic artificial stone repair material, comprising:
[0050] S100, first accurately weigh the magnesium material and phosphorus material in the repair component, then weigh the retarding material, inorganic active additive material and aggregate in the regulating component respectively, mix them according to the proportion and stir them evenly to obtain a solid mixture.
[0051] S200, mix the coloring material and the dispersion liquid in a mass ratio of 1:1, grind them in a three-roll grinder for 90 minutes in advance, and adjust them into a water-based color paste
[0052] S300, weigh 17% of the mass of the repair component in mixing water, drop the prepared water-based color paste into the water in small amounts and multiple times until there is no obvious color difference with the inorganic artificial stone, and mix evenly to obtain a toning solution.
[0053] S400, mixing the solid mixture with the toning liquid for 2 minutes, during which white color paste or black color paste is added in small amounts and multiple times, and fine-tuned until there is no color difference, to obtain the inorganic artificial stone repair material.
[0054] Example 3
[0055] The inorganic artificial stone repair material proposed by the present invention is firstly weighed according to the mass percentage of the magnesium material and the phosphorus material in the repair component, wherein the regulating component is additionally weighed and added based on the mass of the repair component being 100%, specifically as follows:
[0056] Repair components: magnesium oxide powder 75%, potassium dihydrogen phosphate 25%, the sum of the two is 100%.
[0057] Regulating components: borax 5%, white silica fume 5%, quartz sand 40%, white color paste 0.4%, black color paste 0.2%, tap water 17%.
[0058] like Figure 1 As shown, the embodiment of the present invention also provides a method for preparing an inorganic artificial stone repair material, comprising:
[0059] S100, first accurately weigh the magnesium material and phosphorus material in the repair component, then weigh the retarding material, inorganic active additive material and aggregate in the regulating component respectively, mix them according to the proportion and stir them evenly to obtain a solid mixture.
[0060] S200, mix the coloring material and the dispersion liquid in a mass ratio of 1:1, grind them in a three-roll grinder for 90 minutes in advance, and adjust them into a water-based color paste
[0061] S300, weigh 17% of the mass of the repair component in mixing water, drop the prepared water-based color paste into the water in small amounts and multiple times until there is no obvious color difference with the inorganic artificial stone, and mix evenly to obtain a toning solution.
[0062] S400, mixing the solid mixture with the toning liquid for 2 minutes, during which white color paste or black color paste is added in small amounts and multiple times, and fine-tuned until there is no color difference, to obtain the inorganic artificial stone repair material.
[0063] Example 4
[0064] The inorganic artificial stone repair material proposed by the present invention is firstly weighed according to the mass percentage of the magnesium material and the phosphorus material in the repair component, wherein the regulating component is additionally weighed and added based on the mass of the repair component being 100%, specifically as follows:
[0065] Repair components: magnesium oxide powder 75%, potassium dihydrogen phosphate 25%, the sum of the two is 100%.
[0066] Regulating components: borax 5%, white silica fume 5%, quartz sand 60%, white color paste 0.4%, black color paste 0.2%, tap water 17%.
[0067] like Figure 1 As shown, the embodiment of the present invention also provides a method for preparing an inorganic artificial stone repair material, comprising:
[0068] S100, first accurately weigh the magnesium material and phosphorus material in the repair component, then weigh the retarding material, inorganic active additive material and aggregate in the regulating component respectively, mix them according to the proportion and stir them evenly to obtain a solid mixture.
[0069] S200, mixing the coloring material and the dispersion liquid in a mass ratio of 1:1, grinding them in a three-roll grinder for 90 minutes in advance, and adjusting them into a water-based color paste.
[0070] S300, weigh 17% of the mass of the repair component in mixing water, drop the prepared water-based color paste into the water in small amounts and multiple times until there is no obvious color difference with the inorganic artificial stone, and mix evenly to obtain a toning solution.
[0071] S400, mixing the solid mixture with the toning liquid for 2 minutes, during which white color paste or black color paste is added in small amounts and multiple times, and fine-tuned until there is no color difference, to obtain the inorganic artificial stone repair material.
[0072] Comparative Example 1
[0073] This comparative example uses traditional silicate cement as a repair material. First, white silicate cement as the main component is weighed, wherein the regulating component is calculated based on the mass of the main component as 100%, and additional weight is added, as follows:
[0074] Control components: white silica fume 5%, polycarboxylic acid high-efficiency water reducer 5%, tap water 17%.
[0075] like Figure 2 As shown, the embodiment of the present invention also provides a method for preparing a traditional inorganic artificial stone repair material, comprising:
[0076] S100, first accurately weigh the white silicate cement in the main component, then weigh the white silica fume and polycarboxylic acid high-efficiency water reducer in the regulating component respectively, mix them according to the proportion and stir them evenly to obtain a solid mixture.
[0077] S200, mixing the coloring material and the dispersion liquid in a mass ratio of 1:1, grinding them in a three-roll grinder for 90 minutes in advance, and adjusting them into a water-based color paste.
[0078] S300, weigh 17% of the mass of the main components of mixing water, drop the prepared color paste into the water in small amounts several times until there is no obvious color difference with the inorganic artificial stone, and mix evenly to obtain a toning solution.
[0079] S400, mixing the solid mixture with the coloring liquid for 2 minutes, during which time white color paste or black color paste is added in small amounts and multiple times, and fine-tuned until there is no color difference, to obtain the traditional silicate cement repair material.
[0080] Comparative Example 2
[0081] This comparative example uses traditional silicate cement as a repair material. First, white silicate cement as the main component is weighed, wherein the regulating component is calculated based on the mass of the main component as 100%, and additional weight is added, as follows:
[0082] Control components: white silica fume 5%, quartz sand 40%, polycarboxylic acid high-efficiency water reducing agent 5%, tap water 17%.
[0083] like Figure 2 As shown, the embodiment of the present invention also provides a method for preparing a traditional inorganic artificial stone repair material, comprising:
[0084] S100, first accurately weigh the white silicate cement in the main component, then weigh the white silica fume, quartz sand and polycarboxylic acid high-efficiency water reducer in the regulating component respectively, mix them according to the proportion and stir them evenly to obtain a mixture for use.
[0085] S200, mixing the coloring material and the dispersion liquid in a mass ratio of 1:1, grinding them in a three-roll grinder for 90 minutes in advance, and adjusting them into a water-based color paste.
[0086] S300, weigh 17% of the mass of the main components of mixing water, drop the prepared color paste into the water in small amounts several times until there is no obvious color difference with the inorganic artificial stone, and mix evenly to obtain a toning solution.
[0087] S400, mixing the solid mixture with the coloring liquid for 2 minutes, during which time white color paste or black color paste is added in small amounts and multiple times, and fine-tuned until there is no color difference, to obtain the traditional silicate cement repair material.
[0088] The setting time (initial setting time) of each embodiment and comparative example was tested according to GB / T 1346-2011 "Test Method for Water Consistency, Setting Time and Stability of Cement Standard Consistency"; the compressive strength and flexural bond strength of each embodiment and comparative example 3h and 3d were tested according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar". The test results of the above embodiments and comparative examples are shown in Table 1.
[0089] In particular, the manufacturing process of the flexural bonding strength test specimen is as follows: a regular rectangular block of inorganic artificial stone with a size of 40*40*80 mm is cut and placed in a mold of 40*40*160 mm, and the inorganic artificial stone repair material of the present invention is poured at the other end.
[0090] Table 1
[0091]
[0092] It can be seen from Table 1 that:
[0093] 1. The setting time of Examples 1-4 is all within the range of 16-20 minutes, which is about 130 minutes shorter than that of Comparative Examples 1-2. This shows that the inorganic artificial stone repair material achieves the rapid repair service of inorganic artificial stone.
[0094] 2. Compared with comparative examples 1-2 which did not form strength at 3h, the compressive strength of embodiments 1-4 at 3h could reach above 17MPa, and the flexural bonding strength could reach above 2MPa, which indicates that the inorganic artificial stone repair material has good early mechanical properties.
[0095] 3. The compressive strength and flexural bond strength at 3h of Examples 1-4 reach and exceed the compressive strength and flexural bond strength at 3d of Comparative Examples 1-2, and the compressive strength and flexural bond strength at 3d of Examples 1-4 are still significantly improved compared to 3h.
[0096] In summary, the repair material of the present invention is a chemically bonded magnesium phosphate-based inorganic gelling material. The magnesium material can come from magnesite fired at about 800°C or brucite ore directly ground into powder. Compared with traditional cement-based repair materials, the carbon emissions are greatly reduced, and the energy consumption and repair costs are significantly reduced. At the same time, inorganic artificial stone, as a cement-based artificial stone, has extremely strong compatibility with the repair material of the present invention, which is specifically manifested in the high interface bonding strength between the two, and no obvious weak area will be formed; the repair material of the present invention can solidify and harden in a short time to form strength and start service; the repair material of the present invention is pure white or a similar color, which is operable, and can be matched with a color adjustment material to flexibly repair inorganic artificial stones of various colors without color difference; the repair material of the present invention has high fluidity, can achieve the goals of self-leveling and self-compacting, and is suitable for various types of damage or cracks of different widths of inorganic artificial stones; the repair material of the present invention has good wear resistance, acid and alkali resistance, and is suitable for various indoor and outdoor decoration environments. Furthermore, the setting time of the inorganic artificial stone repair material can be adjusted in the range of 5-40min, and the 3h compressive strength can reach 35.1MPa. At the same time, the regulating mechanism of the inorganic artificial stone repair material by the regulating components is as follows: the retarding materials such as sodium citrate and borax, citric acid and boric acid will form BOC chains by complexation, and reduce the dissolution rate of magnesium ions through the steric hindrance effect, showing a synergistic effect; the inorganic active additives can be used to improve the internal pore structure of the material, fill larger harmful pores, and optimize the physical and chemical properties of the material; the aggregates are selected according to the material, and the quartz sand particle size is selected to be consistent with the aggregates used for the damaged inorganic artificial stone. The selection of continuously graded aggregates can further optimize the service performance of the repair material; the coloring material is pre-mixed into a water-based color paste, which is more operable, easier to control and easier to disperse than adding color powder to the mixing water. In summary, under the synergistic effect of the retarding materials, inorganic active additives, aggregates and coloring materials, the service performance and aesthetics of the repair material are taken into account. The inorganic artificial stone repair material and preparation method thereof provided by the present invention fill the gap in after-sales repair of inorganic artificial stone, while achieving the technical goals of fast repair, excellent service and good appearance, and greatly promoting the marketization of inorganic artificial stone decorative applications.
[0097] It should be understood that, although the steps in the flowchart of the accompanying drawings are displayed in sequence as indicated by the arrows, these steps are not necessarily executed in sequence in the order indicated by the arrows. Unless otherwise specified herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders. Moreover, at least a part of the steps in the flowchart of the accompanying drawings may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn or alternately with other steps or at least a part of the sub-steps or stages of other steps.
[0098] The above description is only a partial implementation method of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.
Claims
1. An inorganic artificial stone repair material, characterized in that: It includes a repair component and a regulating component. The repair component is measured in percentage by mass and includes: 40%-80% of magnesium material and 20%-60% of phosphorus material; additionally added regulating components, based on 100% of the mass of the repair component, include: 2%-10% of retarding material, 2%-10% of inorganic active additive material, 0%-60% of aggregate, 0%-2% of coloring material and 12%-25% of mixing water.
2. The inorganic artificial stone repair material according to claim 1, characterized in that: The magnesia material includes one or more of brucite, high temperature fired magnesium-containing ore powder and pure magnesium oxide chemical powder.
3. The inorganic artificial stone repair material according to claim 2, characterized in that: The magnesium materials are all in white powder form, and the MgO content in the chemical composition is higher than 50%.
4. The inorganic artificial stone repair material according to claim 1, characterized in that: The phosphorus material is one or more of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, ammonium monohydrogen phosphate, potassium monohydrogen phosphate, and sodium monohydrogen phosphate.
5. The inorganic artificial stone repair material according to claim 4, characterized in that: The chemical purity of the phosphorus materials is higher than 99.0%.
6. An inorganic artificial stone repair material according to any one of claims 1 to 5, characterized in that: The retarding material is one or two of borax, boric acid, sodium citrate and citric acid, and the chemical purity of the retarding material is higher than 99.0%.
7. An inorganic artificial stone repair material according to any one of claims 1 to 5, characterized in that: The inorganic active additive material is one or both of silica fume and metakaolin, and both are white particles or powders.
8. An inorganic artificial stone repair material according to any one of claims 1 to 5, characterized in that: The aggregate is quartz sand with continuous grading, and the mesh size ranges from 10 mesh to 100 mesh.
9. An inorganic artificial stone repair material according to any one of claims 1 to 5, characterized in that: The coloring material is one or more of titanium dioxide, iron black powder, iron red powder, iron yellow powder and iron brown powder.
10. A method for preparing a repairing material of an inorganic artificial stone according to any one of claims 1 to 9, characterized in that: include: S100, weighing the magnesium material and the phosphorus material in the repair component, the retarding material, the inorganic active additive material and the aggregate in the regulating component respectively, mixing them in proportion and stirring them evenly to obtain a solid mixture; S200, mixing the coloring material and the dispersion liquid in a mass ratio of 1:1, grinding in advance in a three-roll grinder for 45-120 minutes, and adjusting to a water-based color paste; S300, weighing 12%-25% of the mass of the repair component, adding the water-based color paste to the water in small amounts and multiple drops until there is no obvious color difference between the water-based color paste and the inorganic artificial stone, and mixing evenly to obtain a toning solution; S400, mixing the solid mixture with the toning solution for 1-3 minutes, during which the color paste can be dripped in small amounts multiple times to fine-tune until there is no color difference, thereby obtaining the inorganic artificial stone repair material.
